Geographic information system based decision support system for renewable energy development an Indonesian case study. - Sah, Bhuwneshwar Prasad (Metro Manila, Philippines Asian Development Bank, 2017)
The Asia and Pacific region is blessed with abundant renewable energy resources. Ironically, 420 million of its people still have no access to electricity, which makes tapping renewable energy an urgent necessity. The GIS-based decision support system (DSS) is a tool designed to help quantify renewable energy sources in a geographical area. Using Bali, Indonesia as case study, the tool estimates the technical potential and creates the right mix of renewable energy (solar, wind, biomass, hydropower, and geothermal) to meet Balis specific energy needs. Find out more about this GIS based system and its potential as a practical tool to support the regions rapid deployment of renewable energy technologies.
Keywords: Renewable energy sources; Energy Policy, Economics and Management; Electronic books